Daily Chronic Intermittent Hypobaric Hypoxia Does Not Induce Chronic Increase in Pulmonary Arterial Pressure Assessed by Echocardiography - Jeremias Götschke; Pontus Mertsch; Nikolaus Kneidinger; Diego Kauffmann-Guerrero; Jürgen Behr; Rudolf Maria Huber; Frank Reichenberger; Katrin Milger (Canadian Respiratory Journal)
Chronic hypoxia causes pulmonary vascular remodeling resulting in persistently increased pulmonary arterial pressures (PAP) even after return to normoxia. Recently, interest in chronic intermittent hypobaric hypoxia (CIHH) was raised because it occurs in subjects working at high altitude (HA) but living in lowland. However, effects of daily CIHH on PAP are unknown. In this pilot study, we included 8 healthy subjects working at (2650 m) each workday for 8-9 h while living and sleeping at LA and 8 matched control subjects living and working at LA. Cardiorespiratory measurements including echocardiography at rest and during exercise were performed at LA (Munich, 530 m) and HA (Zugspitze, 2650 m). Hemoglobin was higher in CIHH subjects. LA echocardiography showed normal right and left cardiac dimensions and function in all subjects. Systolic PAP (sPAP) and tricuspid annular plane systolic excursion (TAPSE) at rest were similar in both groups. Resting blood gas analysis (BGA) at HA revealed decreased pCO2 in CIHH compared to controls (HA: 28.4 versus 31.7 mmHg, p=0.01). During exercise, sPAP was lower in CIHH subjects compared to controls (LA: 28.7 versus 35.3 mmHg, p=0.02; HA: 26.3 versus 33.6 mmHg, p=0.04) and peripheral oxygen saturation (SpO2) was higher. In sum, subjects exposed to CIHH showed no signs of pulmonary vascular remodeling.